Success begets success! Exploring the carry-over effects of total underwriting effort on post-IPO issuer firm outcomes - Cheng, L.T.W.; Sharma, Piyush; Yan, S. (2023)
Past research on initial public offers (IPO) marketing highlights the positive impact of underwriters’ efforts on the post-IPO marketing and financial outcomes for the IPO issuer firms but the exact mechanism underlying these ‘carry-over’ effects is still not clear. We address this important research gap by exploring the impact of total underwriting effort (i.e., combined efforts by underwriters and other players involved in IPO issuance) on the issuer firms’ post-IPO performance and the mediating role of IPO issuer satisfaction in this process. We test all the hypotheses using data from the China Stock Market and Accounting Research (CSMAR) database on 2,013 IPOs listed on Shanghai Stock Exchange (SSE) and Shenzhen Stock Exchange (SZSE). Our findings provide a holistic view of the complex marketing forces that drive the total underwriting effort on the IPO issuer firms’ post-IPO performance, and the focal role played by IPO issuer satisfaction in this process.